Representation of the Female Body and Sexuality in the Book Fathul Izar by KH. Abdullah Fauzi: A Study of Andrea Dworkin's Radical Feminism - Muhammad Mugni Ulum; Maman Abdul Djaliel; Rohanda Rohanda (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
This study aims to analyze the representation of women's bodies and sexuality in KH. Abdullah Fauzi's book Fathul Izar through the perspective of Andrea Dworkin's radical feminism. Specifically, this study aims to uncover how the text functions as an instrument of patriarchal control that reduces women to sexual objects and perpetuates a system of subordination in the private sphere. The method used is qualitative with a content analysis design through a critical-interpretive approach. Radical feminist theory was chosen because it views sexuality as an arena of male domination, where women's bodies are defined based on their physical utility. Data were collected through a literature review of the main text of Fathul Izar and related academic literature. The results show that women's bodies are represented subordinately as reproductive objects through the metaphor of